Analysis and Development of HOTS-Based Reaction Rate Problem Instruments Using the Rasch Model - Damanik, Santri Angelia; Saragih, Inovayani; Darmana, Ayi (Universitas Lampung, 2024)
The research carried out was research and development to obtain instruments for HOTS-based reaction rates. The development of this item instrument is carried out first by following the steps for preparing HOTS questions which of course also pay attention to the characteristics of the HOTS questions. The next step is to analyze the item items based on the response pattern of the answers given by the students using the Rasch model assisted by the WINSTEPS 3.73 application. In this study the results of student answers were analyzed based on eight (8) types of output tables. Based on the analysis using the Rasch model, the following results are obtained: 1) Results of the Output tables item fit order obtained Outfit values: MNSQ (0.70 – 1.61); ZSTD (-1.3 – 2.0) and Pt Measure Corr (0.29 – 0.64). 2) Summary statistics: Person Reliability (0.74 & 0.76) enough category; Item Reliability (0.71 & 0.73) is sufficient category, and Cronbach Alpha Reliability (0.81) is very good category. The final result is concluded, as many as 1 question out of 20 questions developed (5%) fall into the misfit category.Keywords: Reaction Rate Question Instrument, HOTS, Rasch Model.DOI: 10.23960/jppk.v13.i1.2024.08